Strengthening the Pedagogical Competence of English Education Students through Information Gap Activities Design Training - Sirajuddin Kamal; Novita Triana; Elvina Arapah; Muhammad Rizky Kusuma Dewa; Zidyah Ahadiyah; Mohamed Ebrahim (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
The low English proficiency among the Indonesian society is partly influenced by the dominance of learning approaches that focus on grammar and vocabulary memorization, thereby limiting students' opportunities to use the language in meaningful communication. Communicative Language Teaching (CLT) is an approach that emphasizes language use for authentic communication purposes, with information gap activities (IGA) serving as one of the primary techniques to foster classroom interaction. This community service activity aims to enhance the pedagogical competence of pre-service English teachers in designing and implementing CLT-based IGA. The activity was conducted using the Participatory Action Research (PAR) method, involving students from the English Education Study Programs at Universitas Sari Mulia and Universitas Lambung Mangkurat. The needs analysis results indicated that most participants lacked an adequate understanding of the IGA concept and still tended to employ traditional, teacher-centered learning activities. Through this training, participants gained an understanding of CLT principles and skills in designing communication-oriented activities centered on information exchange. Following the training, participants were capable of developing and practicing various information gap activities, such as Jigsaw Reading, Missing Schedule, and Spot the Differences, integrated into communicative learning scenarios. The questionnaire results demonstrated that this training strengthened the pedagogical competence of pre-service English teachers in designing communicative, interactive, and student-centered learning. Therefore, similar training needs to be conducted sustainably to support the quality improvement of communicative English language learning.